The Complete Plastome Sequences of Four Orchid Species: Insights into the Evolution of the Orchidaceae and the Utility of Plastomic Mutational Hotspots - Niu, Zhitao; Xue, Qingyun; Zhu, Shuying; Sun, Jing; Liu, Wei; Ding, Xiaoyu (Frontiers in Plant Science, 2017)
Orchidaceae (common name: orchids) is the largest family in monocots, comprising about 25,000 species in 880 genera and five subfamilies. Many orchids are of great values because of their beautiful and long-lasting flowers. However, phylogenetic relationships among the five orchid subfamilies remain unresolved. The major dispute centered on whether the three one-stamened subfamilies, Epidendroideae, Orchidoideae, and Vanilloideae, are monophyletic or paraphyletic. Moreover, the plastome structural changes and effective genetic loci at the species-level phylogenetics of orchids have been rarely documented. In this study, we compared 53 orchid plastomes, including four newly sequenced ones that represent four remote genera: Dendrobium, Goodyera, Paphiopedilum, and Vanilla. These four plastomes differ from one another not only in their lengths of inverted repeats (IRs) and small single copy (SSC) regions but also in the retention of NDH genes. Comparative analyses of the orchid plastomes revealed that the expansion of IRs in Paphiopedilum and Vanilla is associated with loss of NDH genes. In orchid plastomes, mutational hotspots are genus-specific. With carefully estimated, we proposed that the three loci: 5’trnK-rps16, trnS-trnG and rps16-trnQ could be a powerful marker for the genera within Epidendroideae, and clpP-psbB, rps16-trnQ for Cypripedioideae. After analysis of partitioned dataset, our plastid phylogenomic trees were congruent in topologies, in which two one-stamened subfamilies (i.e., Epidendroideae and Orchidoideae) were placed as sister to a multi-stamened subfamily (i.e., Cypripedioideae) rather than to the other one-stamened subfamily (Vanilloideae), suggesting that the living one-stamened orchids be paraphyletic.